Monographie der palaearktischen Lonchaeidae (Diptera). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1959)
Nomenclatural Actsgracilis Czerny, 1934 (Chaetolonchaea), Lectotypepellicula Morge, 1959 (Chaetolonchaea), spec. n.